PROFIL PELAJAR PANCASILA AS A MODEL FOR STRENGTHENING CHARACTER IN THE MERDEKA CURRICULUM - Irawan, Hendri; Siti Masyitoh, Iim; Rahmat, Rahmat; Darmawan, Cecep; Anggraeni, Leni (Universitas Negeri Semarang, 2024)
Character education has become an important concern in developing the education system in Indonesia over the past decade. To face complex challenges in an ever-evolving society, strengthening character education is important in shaping individuals with integrity, ethics and good personality. Therefore, this study aims to analyse and evaluate the innovation of the character education strengthening program model implemented in the curriculum in Indonesia. The approach of this research used descriptive qualitative with literature study method to collect information from various reliable sources such as scientific journals, books, and official publications. The results of this analysis and evaluation discuss various innovations in the character education strengthening model implemented in Indonesia during this period, including the approaches, strategies, and methods used. The findings of this research are. Firstly, various innovative models of strengthening character education have been implemented in Indonesia, including value-based learning approaches, character education through extracurricular activities, and the integration of character education in all subjects. Secondly, implementing these innovations has a positive impact on shaping students' character, such as increasing positive attitudes, social care, ethics, and integrity. However, there are also challenges including the lack of understanding and full involvement of all education stakeholders. The study concludes that the integration of character education should be an integral part of the curriculum at all levels of education. This research contributes to the development of character education in Indonesia by presenting innovative models of strengthening character education that have been implemented and highlighting the challenges that need to be overcome